ANALISIS HILANGNYA MEREK I AM GEPREK BENSU PADA PANGKALAN DATA KEKAYAAN INTELEKTUAL (PDKI) BERDASARKAN UNDANG-UNDANG NOMOR 20 TAHUN 2016 TENTANG MEREK DAN INDIKASI GEOGRAFIS: Analysis of the Disappearance of I Am Geprek Bensu Brand in the Intellectual Property Database under Law Number 20 of 2016 concerning Trademarks and Geographical Indications - Deva Annisa Nur Yuliana; Rakhmita Desmayanti; Bahasa Indonesia (Faculty of Law, Universitas Trisakti, 2024)
The occurrence of disputes over the use of the